Streptozotocin Induces Alzheimer’s Disease-Like Pathology in Hippocampal Neuronal Cells via CDK5/Drp1-Mediated Mitochondrial Fragmentation - Park, Junghyung; Won, Jinyoung; Seo, Jincheol; Yeo, Hyeon-Gu; Kim, Keonwoo; Kim, Yu Gyeong; Jeon, Chang-Yeop; Kam, Min Kyoung; Kim, Young-Hyun; Huh, Jae-Won; Lee, Sang-Rae; Lee, Dong-Seok; et al. (Frontiers in Cellular Neuroscience, 2020)
Aberrant brain insulin signaling plays critical roles in the pathology of Alzheimer’s disease (AD). Mitochondrial dysfunction plays a role in the progression of AD, with excessive mitochondrial fission in the hippocampus being one of the pathological mechanisms of AD. However, the molecular mechanisms underlying the progression of AD and mitochondrial fragmentation induced by aberrant brain insulin signaling in the hippocampal neurons are poorly understood. Therefore, we investigated the molecular mechanistic signaling associated with mitochondrial dynamics using streptozotocin (STZ), a diabetogenic compound, in the hippocampus cell line, HT-22 cells. In this metabolic dysfunctional cellular model, hallmarks of AD such as neuronal apoptosis, synaptic loss, and tau hyper-phosphorylation are induced by STZ. We found that in the mitochondrial fission protein Drp1, phosphorylation is increased in STZ-treated HT-22 cells. We also determined that inhibition of mitochondrial fragmentation suppresses STZ-induced AD pathology. Furthermore, we found that phosphorylation of Drp1 was induced by CDK5, and inhibition of CDK5 suppresses STZ-induced mitochondrial fragmentation and AD pathology. Therefore, these findings indicate that regulation of mitochondrial morphology and function may be a potential therapeutic strategy for treating abnormal metabolic functions associated with the pathogenesis of AD.